Answer:
1050
Step-by-step explanation:
First, it would help to simplify each side more:
Left side: 36 + 3(4x - 9) = 36 + 12x - 27 = 12x + 9
Right side: c(2x + 1) + 25 = 2cx + c + 25
Write the simplified equation:
12x + 9 = 2cx + c + 25
Usually when there is no solution, the coefficients of the variable on both sides are the same, so we can make the coefficient if x on the right side into 12:
2cx >>> 12x
Then, c must equal 6 to make this true.
The answer is choice (C).
Answer:
All answers in this set can be written in the form y=f(x).
Answer:
3.5
Step-by-step explanation: Just trust sweetie